2013
DOI: 10.7860/jcdr/2013/4808.2746
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Nucleolar Organizer Regions-As a Tumour Proliferative Marker in Cervical Smears

Abstract: Aim: To study the Argyrophilic Nucleolar Organizer Regions (AgNOR) as a cell proliferative marker in cervical smears and to assess its counts with the severity of the lesions on Papanicolaou (PAP) stained cervical smears. Material and Method:The present study was a prospective experimental study which was carried out at Jawaharlal Nehru Medical College in a span of 2 years. 50 high risk cases were selected from the Gynaecological OPD. The cervical smears were collected in pairs, one for the conventional PAP st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…concluded that stage is the most important prognostic factor with 5-year overall survival rates varying on stage: FIGO stage I -79%, II -37%, III / IV -less than 9% [9]. Studies reflecting on different types of cervical cancer [10][11][12], ovarian tumours [13][14][15][16] were reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…concluded that stage is the most important prognostic factor with 5-year overall survival rates varying on stage: FIGO stage I -79%, II -37%, III / IV -less than 9% [9]. Studies reflecting on different types of cervical cancer [10][11][12], ovarian tumours [13][14][15][16] were reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…Mean AgNOR count: In this study, the mean AgNOR count increases as disease progresses from chronic cervicitis to CIN I to CIN II to CIN III to squamous cell carcinoma. Samarth [8] et al (2012) conducted a study on 50high risk women. They took 2 cervical smears.…”
Section: Accuracy Of Colposcopymentioning
confidence: 99%